2022
DOI: 10.1186/s13068-022-02118-w
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive laboratory evolution and shuffling of Escherichia coli to enhance its tolerance and production of astaxanthin

Abstract: Background Astaxanthin is one of the strongest antioxidants in nature and has been widely used in aquaculture, food, cosmetic and pharmaceutical industries. Numerous stresses caused in the process of a large scale-culture, such as high acetate concentration, high osmolarity, high level of reactive oxygen species, high glucose concentration and acid environment, etc., limit cell growth to reach the real high cell density, thereby affecting astaxanthin production. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Another study found that the mutant RpoC H419P of the RNA polymerase subunit RpoC in an evolved E. coli was associated with its increased tolerance to octanoic acid (C8) and increased C8 production (Chen et al 2020). Using ALE coupled with genome restructuring technology, we obtained a robust astaxanthinproducing E. coli that was tolerant to large-scale culture high-density fermentation conditions (low pH, high osmolality (high NaCl concentration), high acetate concentration, and high reactive oxygen species concentration (high concentration of H 2 O 2 )), and found that rnb, envZ, and recC were associated with the robustness of the strain (Lu et al 2022).…”
Section: Adaptive Laboratory Evolutionmentioning
confidence: 99%
“…Another study found that the mutant RpoC H419P of the RNA polymerase subunit RpoC in an evolved E. coli was associated with its increased tolerance to octanoic acid (C8) and increased C8 production (Chen et al 2020). Using ALE coupled with genome restructuring technology, we obtained a robust astaxanthinproducing E. coli that was tolerant to large-scale culture high-density fermentation conditions (low pH, high osmolality (high NaCl concentration), high acetate concentration, and high reactive oxygen species concentration (high concentration of H 2 O 2 )), and found that rnb, envZ, and recC were associated with the robustness of the strain (Lu et al 2022).…”
Section: Adaptive Laboratory Evolutionmentioning
confidence: 99%
“…Based on these results, they knocked out the oxidative-stress-related genes ( uspE and yggE ) to elevate reactive oxygen species (ROS) in E. coli cells, thereby stimulating the production of astaxanthin to cope with oxidative stress [ 113 ]. Similarly, the knockout of some other pressure response proteins can also improve the production of astaxanthin to varying degrees [ 141 ]. Through transcriptome analysis, Wang et al [ 25 ] found that the mevalonate and ergosterol biosynthetic pathway, oxidative PPP, and antioxidant system were significantly down-regulated in the engineering of Y. lipolytica with astaxanthin overproduction.…”
Section: Metabolic Engineering Strategies Of Model Microorganisms For...mentioning
confidence: 99%
“…Adaptive laboratory evolution (ALE) proved to be a valuable approach to enhance the phenotype or physiological attributes of strains [34]. Indeed, researchers successfully identified numerous gene targets by using ALE; for example, the overexpression of the class E protein gene Did2 led to a 2.1-fold increase in β-carotene yields [37][38][39][40]. By employing ALE, our group also identified two novel gene targets, cho2 and pfk1, whose regulation can increase lycopene yield by 3.4 and 5.1 times, respectively [41,42].…”
Section: Technology For Discovering Novel Gene Targetsmentioning
confidence: 99%